1985
DOI: 10.1093/clinchem/31.10.1689
|View full text |Cite
|
Sign up to set email alerts
|

Adenylate kinase: an oncodevelopmental marker in an animal model for human prostatic cancer.

Abstract: Data are presented demonstrating that adenylate kinase (AK; EC 2.7.4.3) is an oncodevelopmental enzyme in the prostate of Copenhagen rats. We selected the Dunning tumor (dorsal rat prostate) as a model system because it most nearly approximates the human pathology. Four sublines of the tumor (R3327-H, R3327-AT, MAT Lu, and MAT LyLu) were studied. The tumor sublines were maintained as solid tumors in syngeneic rats and as monolayers in tissue culture. AK activity appeared in conjunction with malignant transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Although the increased expression of AK2 has been found in breast CSC [49] and prostate cancer cells [50], another study states that AK2 is rather a negative regulator of tumor growth [51].On the other hand, it has been reported that the up-regulation of AK2 provides the energy required for the proliferation of hematopoietic stem cells [52] and plays an important role in communication between mitochondria and nucleus [18]. AK2 deficiency impairs embryonic development and causes hematopoietic defects indicating the significance of AK2 in the energy metabolism of normal stem cells [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Although the increased expression of AK2 has been found in breast CSC [49] and prostate cancer cells [50], another study states that AK2 is rather a negative regulator of tumor growth [51].On the other hand, it has been reported that the up-regulation of AK2 provides the energy required for the proliferation of hematopoietic stem cells [52] and plays an important role in communication between mitochondria and nucleus [18]. AK2 deficiency impairs embryonic development and causes hematopoietic defects indicating the significance of AK2 in the energy metabolism of normal stem cells [52,53].…”
Section: Discussionmentioning
confidence: 99%